MBboard: validity and reliability of a new tool developed to evaluate specific strength in rock climbers - Marino, T.; Coelho, D.; Lima-Silva, A. E.; Bertuzzi, R. (Journal of Human Kinetics, 2021)
In the present study, we analysed the validity and reliability of a new tool designed to assist the measurement of maximal upper-limb strength in rock climbers in a specific way, named MB board. The MBboard consists of an artificial small climbing hold affixed to a wooden board, which is connected to any cable-motion strength equipment to determine the maximum dynamic strength (MBboard-1RM). Ten male rock climbers (Rock Climbing Group, RCG = 10) and ten physically active men (Control Group, CG = 10) performed, on three separate occasions, a familiarization session with procedures adopted during MBboard-1RM testing and two experimental trials (i.e., test and retest) to determine the construct validity and reliability of the MBboard during unilateral seated cable row exercise. In the first trial, the electromyographic activity (EMG) was recorded from the flexor digitorum superficialis. The self-reported climbing ability was also recorded. The RCG had superior p erformance (i.e. 37.5%) and EMG activity (i.e. 51%) in MBboard-1RM testin g when compared with the CG (p < 0.05). There was a significant correlation between the MBboard-1RM results and climbing ability (r > 0.72, p < 0.05). Intraclass correlation coefficient analysis revealed good reliability within trials (ICC > 0.79, p < 0.05). These findings suggest that the MBboard is a va lid and reliable tool to assess rock climbing-specific maximal strength. The validity of MBboard-1RM appears to be related to the finger flexor muscles activation, probably reflecting the specific adaptations resulting from long-term practice of this sport discipline.